Identification of flavonoids by HPLC-MS in fruit waste of Latin America: A systematic review (Scientia Agropecuaria, 2023)
Fruit waste is rich in phenolic compounds, including flavonoids with pharmacological potential for health, nutraceutical and technological properties. To characterize them, High Performance Liquid Chromatography-Mass Spectrometry (HPLC-MS) was used, used for its high separation efficiency by HPLC and structural information from MS, a technique that allows analyzing a wide range of analytes in plant matrices. This study aims was to perform a systematic analysis based in SCOPUS of scientific productions of studies on techniques for detection and identification of flavonoids by HPLC-MS in fruit waste available in Latin America, between the years 2010-2022. Thus, the countries with the highest scientific production are Brazil (58.9%), Mexico (16.1%), Chile (9.2%), Argentina (7.1%) and Colombia (3.8%). There were also studies in collaboration with researchers from the USA and Europe. A total of 15.1% of the studies used HPLC-MS for determining these compounds, generally related to by-products of native or non-traditional fruits. It is known that agro-industrial waste matrices are chemically complex, being necessary analytical techniques such as HPLC-MS, which awakens interest for their study and the possibility of being isolated from vegetable by-products such as fruits. This is a green technology alternative to achieve sustainable use of this waste and be exploited by the food industry.
Keywords: flavonoids; High Performance Liquid Chromatography-Mass Spectrometry; fruit waste; detection technique; Latin America